The risk of transmitting antibiotic resistance through endophytic bacteria - Scaccia, Nazareno (2021)
Antibiotic resistance is a global human health threat distributed across humans, animals, plants, and the environment. Under the One-Health concept (humans, animals, and environment), the contamination of water bodies and soil by antibiotic-resistant bacteria cannot be dissociated from its potential transmission to humans. Edible plants can be colonized by a vast diversity of bacteria, representing an important link between the environment and humans in the One-Health triad. Based on multiple examples of bacterial groups that comprise endophytes reported in edible plants, and that have close phylogenetic proximity with human opportunistic pathogens, we argue that plants exposed to human-derived biological contamination may represent a path of transmission of antibiotic resistance to humans.